Perception of Students of the Da'wah Management Study Program of UIN Raden Fatah Palembang on the Values of Da'wah in the Film Bid'ah - Emelda; Hidayat HT; Hartika Utami Fitri (Universitas Muhammadiyah Palu, 2026)
This thesis is entitled